Public key infrastructures, services and applications 7th European workshop, EuroPKI 2010, Athens, Greece, September 23-24, 2010, revised selected papers - European PKI Workshop 2010 Athens, Greece); Camenisch, Jan.; Lambrinoudakis, Costas; SpringerLink (Online service). (Berlin New York Springer, 2011)
This book constitutes the thoroughly refereed post-conference proceedings of the 7th European Workshop on Public Key Infrastructures, Services and Applications, EuroPKI 2010, held in Athens, Greece, in September 2010. The 14 revised full papers presented together with an invited article were carefully reviewed and selected from 41 submissions. The papers are organized in topical sections on authentication mechanisms; privacy preserving techniques; PKI & PKC applications; electronic signature schemes; identity management.
Electronic reproduction.
Keywords: Public key infrastructure (Computer security) -- Congresses; Public key cryptography -- Congresses; Data encryption (Computer science) -- Congresses; Computer networks -- Security measures -- Congresses; Electronic book